Multifaceted Interactions Between Endophytes and Plant: Developments and Prospects - Khare, Ekta; Mishra, Jitendra; Arora, Naveen Kumar (Frontiers in Microbiology, 2018)
Microbial endophytes are present in all the known plant species. Their ability to enter and thrive in the plant tissues is unique and represents multidimensional interactions within host plant. Several vital activities of host plant are known to be influenced by presence of endophytes. They can promote plant growth, elicit defence response against pathogen attack and can act as remediator of abiotic stresses. Most of the research depicting endophyte’s behaviour inside host plant assumes their course of action is similar to the plant growth promoting (PGP) microbes present in rhizosphere, however, a new vision towards the difference of rhizosphere environment from that of internal plant tissues is seeking attention. Furthermore, it would be interesting to explore the impact of endosymbiont on the host’s gene expression, metabolism, and physiological aspects essential in conferring resistance against biotic and abiotic stresses. A more enchanting and inexplicable issue with many endophytes that has to be critically evaluated is the ability to produce host-metabolites which could be harnessed at large scale for potential use in medicine, agriculture or industry. In this review, we discuss the concept of endophytism, looking into the latest insights related to multipartite interactions beneficial for host plants and how these association can be explored in the future for sustaining the agriculture, environment, and other vital aspects such as human health.